Research methods and statistics : a critical thinking approach - Sherri L Jackson (New Delhi Cengage, 2024)
The text offers a comprehensive approach to research methods in psychology, suitable for both classes with and without a prerequisite in statistics. It covers essential topics from science and measurement to experimental design and statistical analysis. The emphasis on critical thinking encourages students to evaluate research designs and apply analytical skills. The writing style is straightforward and engaging, aiming to simplify complex concepts. Pedagogical aids, such as learning objectives, key terms, summaries, and exercises, support student learning. The fifth edition includes reorganized chapters, and updated research examples.
Keywords: Statistical Methods